Distribution of epiphytic bryophytes in Wroclaw in relation to urban-use complexes - Fudali, Ewa (Biodiversity: Research and Conservation, 2019)
Studies on epiphytic bryophyte species richness and diversity in various urban-use complexes in Wroclaw (excluding urban forests) were conducted in 2013-2016 to check the research hypothesis that, in spite of the observed phenomenon of return of bryophytic epiphytes to cities, urban parks still favor species richness and the diversity of bryophytic epiphytes in built-up areas. Epiphytes (38 species) were recorded in all distinguished urban-use complexes but with strongly differentiated frequency, and 64% of all the trees colonized with epiphytes were situated either along streets or inside urban green areas (32% in each). It was shown that the highest species richness (89% of all the species found), bryophyte total coverage and values of the diversity indices referred to the latter complex. 20 species revealed preferences to occur mostly or exclusively on trees situated in urban parks. The second urban-use complex, which visibly affected the distribution of epiphytes, was the complex of streets; Tortula muralis occurred only on trees along streets and six other species occurred more frequently in these complexes than in others: Orthotrichum diaphanum, O. pumilum, O. pallens, Ceratodon purpureus, Syntrichia virescens, Bryum argenteum. In general, epiphytes – which were recorded on more than 20 trees – colonized a large number of phorophytes, from 12 to 33. They also showed some tendencies to occupy trunks of some host tree species more frequently than others. Detailed data are provided.